Knowing Good From Bad The Paradox of Neuroticism, Negative Affect, and Evaluative Processing. (article). - Tamir, Maya
There are pragmatic benefits to trait-consistent mood states, especially when people are evaluating new objects within the environment (M. Tamir, M. D. Robinson, & G. L. Clore, 2002). The present studies, involving both naturally occuring (Studies 1 and 2) and manipulated (Study 3) mode states, demonstrated such trait-consistent interactions within the context of neuroticism and negative mood states. Individuals high in neuroticism were faster to make evaluations when a negative mood states like sadness. By contrast , individuals low in neuroticism were faster to make evaluations when in a neural mood state. The present studies demonstrate that although negative mood states are hedonically unpleasant, they can be beneficial in some ways for individuals high in neuroticism. -- (from the author).